FORMULASI EKSTRAK JAHE MERAH (Zingiber officinale var. rubrum) DAN SARI BUAH NAGA MERAH (Hylocereus polyrhizus) TERHADAP SIFAT KIMIA DAN SENSORI PERMEN JELLY Formulation of Red Ginger (Zingiber officinale var. rubrum) Extract and Red Dragon Fruit (Hylocereus polyrhizus) Juice on the Chemical and Sensory Properties of Jelly Candy - Wildan Nur, Aditya; Astuti, Sussi; Kustyawati, Maria Erna; Rizal, Samsul (Jurusan Teknologi Hasil Pertanian, 2024)
Red ginger and red dragon fruit can be used as raw materials for making jelly candy. This research aims to obtain a formulation of red ginger extract and red dragon fruit juice which produces jelly candy with the best chemical and sensory properties. The research was structured in a Complete Randomized Block Design (RAKL) with a single factor and four replications. The comparison treatment of red ginger extract and red dragon fruit juice consisted of four levels, namely 80%:20%(J1), 75%:25%(J2), 70%:30%(J3), 65%:35%(J4), 60%:40%(J5), and 55%:45%(J6). The data were analyzed for homogeneity using the Bartlett test and additional data using the Tuckey test, then the data were analyzed for variance to determine the effect between treatments. If there is a significant effect, the data is analyzed further with the Least Significant Difference Test (LSD) at the 5% level. The results showed that the J6 treatment jelly candy (55% red ginger extract and 45% red dragon fruit juice) was the best treatment which produced a texture score of 3.76 (like), taste score 3.59 (like), aroma score 3.66 (like), and a color score of 4.18 (red), water content of 16.81%, total dissolved solids of 37.80obrix, ash content of 1.97%, reducing sugar content of 8.05%, and activity antioxidants of 34.1% with IC50 of 2478.48 ppm.